2011
DOI: 10.1155/2011/418968
|View full text |Cite
|
Sign up to set email alerts
|

A Suitable Approach to Estimate Cancer Incidence in Area without Cancer Registry

Abstract: Objective. Use of cancer cases from registries and PMSI claims database to estimate Département-specific incidence of four major cancers. Methods. Case extraction used principal diagnosis then surgery codes. PMSI cases/registry cases ratios for 2004 were modelled then Département-specific incidence for 2007 estimated using these ratios and 2007 PMSI cases. Results. For 2007, only colon-rectum and breast cancer estimations were satisfactorily validated for infranational incidence not ovary and kidney cancers. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Many studies have shown the importance of health administrative databases in estimating cancer incidence . Most of these were based on inpatient data to validate cancer cases .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown the importance of health administrative databases in estimating cancer incidence . Most of these were based on inpatient data to validate cancer cases .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have developed methods to identify incident cancers by using health administrative databases . However, given that no ‘date of diagnosis’ variable exists in these databases, the main difficulty remains in the ability to distinguish between prevalent and incident cases, a key issue for etiological cancer studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they strongly depend on the algorithm used to select patients and build the care trajectory. Several studies have assessed the use of administrative databases to detect cancer cases [12,36,37]. Our method selects patients with surgical breast cancer on a combination of diagnosis and procedure codes which can reduce the false positive rate [38].…”
Section: Discussionmentioning
confidence: 99%
“…Incidences from this regional administrative hospital and regional medical information system (further abbreviated as RMIS) have been validated against national incidences from the national register (FRANCIM) [18]. …”
Section: Methodsmentioning
confidence: 99%